Nursing Care for Preschool-Aged Children Experiencing Hospitalization Using Bibliotherapy Innovation Interventions Against Anxiety Problems at Jend. Ahmad Yani Metro City Hospital in 2024 - Kurniati; Kusuma, Anggi (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The purpose of this study was to provide nursing care for preschool-age children who experienced hospitalization using bibliotherapy innovation interventions against anxiety problems at Rsud Jend. Ahmad Yani Metro City in 2024. Method: Data collection methods using pediatric nursing care assessment sheets and anxiety observation sheets using VAS-A. The study used pediatric patients. The results of nursing care were obtained in the evaluation that researchers conducted on client 1 based on the criteria that researchers compiled for 1 diagnosis. Result: The resolved diagnosis is anxiety with both clients both having an anxiety scale of 0 on day 3 after doing bobliotherapy for 3 days. Conclusion: Suggestions for patients and families can apply bibliotherapy either at home, at the hospital or in public places to train children to avoid excessive fear and can be used to improve children's motor and sensory.